Pembaruan Sistem Pendidikan Menurut Muhammad ‘Abduh - Jamaludin Jamaludin; Dahari Dahari (Jurnal Asy-Syukriyyah, 2014)
According to Islamic reformer figures one cause of the decline of Islam is weak and declining quality of Islamic education . To that end , it is necessary to restore the power of the Islamic educational progress of Muslims as a buffer , so that the rise of ideas about education reform Islam followed by the implementation of a change organizers . There are many things that demand held educational reform include: Development of Science , Declining Quality of Education , Less relevance between education and the needs of people who are building . Muhammad Abduh tried to give to the teachings of this nation that the best way to achieve independence is to educate the brain and increase knowledge . Muhammad Abduh education patterns of thought tends to flow progressive . In the field of educational goals , namely universal goals , institutional goals and curricular objectives . The curriculum must specify the mandatory sciences ' ain , not only religious sciences , but also covers general sciences . Educational methods should be accommodating in multiple teaching methods and strongly condemn the method only concerned with memorizing without understanding . the relationship between teachers and students is not limited to any class . eorang teachers should be competent . factors that influence child development are nativist , empirical , and convergent . The position of converging factors by Muhammad Abduh is the integration factor nativist and empirical factors in child development are two factors that affect each other.